2014
DOI: 10.1002/gps.4189
|View full text |Cite
|
Sign up to set email alerts
|

Frontal hypometabolism in elderly breast cancer survivors determined by [18F]fluorodeoxyglucose (FDG) positron emission tomography (PET): a pilot study

Abstract: Purpose The term “chemobrain” is sometimes used to denote deficits in neuropsychological functioning that may occur as a result of cancer treatment. As breast cancer survivors now commonly reach late life, it is not known whether previous exposure to chemotherapy may affect long-term risk for cognitive impairment. To help address this concern, this study tested whether successfully surviving chemotherapy earlier in life was associated with later differences in brain metabolic function as an older adult compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…These frontal regions were also noted to have decreased gray matter from prechemotherapy to postchemotherapy in a previous study by the same authors. 117,118 Findings from fMRI studies are supported by results from complementary techniques, including positron emission tomography, [134][135][136] arterial spin labeling, 137 and electroencephalography (EEG). [138][139][140][141] Magnetic resonance spectroscopy imaging has also provided further insight regarding certain pathophysiologic mechanisms, including inflammation and demyelination.…”
Section: Neuroimagingmentioning
confidence: 93%
“…These frontal regions were also noted to have decreased gray matter from prechemotherapy to postchemotherapy in a previous study by the same authors. 117,118 Findings from fMRI studies are supported by results from complementary techniques, including positron emission tomography, [134][135][136] arterial spin labeling, 137 and electroencephalography (EEG). [138][139][140][141] Magnetic resonance spectroscopy imaging has also provided further insight regarding certain pathophysiologic mechanisms, including inflammation and demyelination.…”
Section: Neuroimagingmentioning
confidence: 93%
“…Chiaravalloti's group reported that brain glucose metabolism in patients with Hodgkin disease was affected after diagnosis and during chemotherapy treatment [ 10 ]. Ponto's group reported that breast cancer survivors treated with chemotherapy may manifest long-term changes in brain glucose metabolism indicative of subtle frontal hypometabolism [ 11 ]. Simó's group reported a long-term decrease in gray matter and white matter volume in chemotherapy-treated patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PET images were analyzed with methods similar to those described previously (Ponto et al, 2014 ; Wyckhuys et al, 2014 ). Each non-contrast CT scan was transformed by rigid, manual co-registration (Jena et al, 2014 ) to align with a standard MRI template, INIA19 Macaca mulatta (Rohlfing et al, 2012 ), with the resultant transformation values individually applied to the PET image from the corresponding data acquisition session to align them to the normalized space.…”
Section: Methodsmentioning
confidence: 99%